Bacterial Lipopolysaccharide Activates Toll-Like Receptor 2 and Toll-Like Receptor 4 Gene Expression in PBMC of Vechur Cattle - Lakshmi, R.; Jayavardhanan, K. K.; Thanislass, J.; Visha, P. (International Journal of Bio-resource and Stress Management, 2021)
Vechur cattle, an indigenous breed of Kerala and it is the smallest cattle breed in the world. They are highly disease resistant. The occurrence of mastitis is very Rare in this breed as compared to crossbred cattle. Rearing of these Vechur breed is more cost effective as they require less feed. Therefore, characterisation of factors involved in the immune system of these breeds might provide an insight into the mechanisms involved in the variation in disease resistance. Toll-like receptors (TLRs) are part of the innate immunity, can recognize the particular pathogens through Pathogen Associated Molecular pattern s (PAMPs) and play important roles in host defense. TLR2 and TLR4 important TLR mediate the responsiveness to bacterial lipopolysaccharide (LPS). Since Vechur cattle are less susceptible to mastitis, in vitro expression assay of TLRs were accessed by challenging the Peripheral Blood Mononuclear Cells (PBMC) with bacterial LPS. Treatment of PBMC with LPS, significantly increased TLR2 and TLR4 genes expression (p≤0.01) in Vechur cattle breed when compared with that of control and crossbred cattle. Among the two TLRs studied, the relative expression of mRNA in Vechur cattle was relatively higher for TLR2 (6.90) than TLR4 (4.24). The higher expression of TLR 2 and TLR 4might contribute maximum innate immune response against the mastitis bacteria in Vechur cattle.